Aetiology and Outcome of Resection and Primary Anastomosis in Multiple Ileal Perforation (Sir Salimullah Medical College Journal, 2022)
Background: Ileal perforation is a very frequent surgical emergency in surgery wards. In tropical country infection is the commonest cause. Repair of perforation, primary repair with loop ileostomy and resection and primary anastomosis are the commonly performed methods.Objectives: To identify the aetiology and assess the outcome of resection and primary anastomosis in multiple ileal Perforation.Study Procedure: This Quasi experimental study was carried out in the Department of Surgery, Rajshahi Medical College Hospital, Rajshahi. 92 patients were included in this study. Thorough clinical, Radiological and biochemical parameters evaluation with postoperative histopathology were performed. All patients treated with resection and primary anastomosis. Different types of Data and variables were recorded through data collection sheet. Mean and frequency of all quantitative and categorical variables were determined.Results: The mean age 42.60±4.44 (age range:18-69) years. Out of 92 patients 74(80.43%) were male and 18(19.56%) were female and ratio was 4.11:1.Presentation were 92(100%) abdominal pain, vomiting 74(80.43%), fever 60(65.21%) and abdominal distension 56(60.86%). Common Cause were typhoid fever 43(46.73%) and nonspecific inflammation 28(30.43%). Patient suffered from wound infection 18(19.44%), dehiscence 7(7.56%), anastomosis leakage 6(6.68%) and 5(5.43%) patient experienced incisional hernia. 74(80.43%) recovered uneventfully, 17(18.47%) recovered with complication and only 1(1.08%) died.Conclusion: Among the infections, typhoid fever is still the prime cause of multiple ileal perforation. Wound infection, wound gap, burst abdomen & primary repair leakage are the common complications. Uneventful outcome is present in majority cases. Delayed presentation, nutritional status and anastomosis from ileocaecal valve are the important deciding factor of worst outcome.Sir Salimullah Med Coll J 2021; 29(2): 153-157